Implementing the EU Water Framework Directive in Norway: Bridging the Gap Between Water Management Networks and Elected Councils?. Issue 4 (7th August 2016) - Hovik, Sissel; Hanssen, Gro Sandkjær
Abstract: To handle the challenge of complex cross-sector and multilevel coordination in the implementation of the European Union Water Framework Directive, Norway has established multilevel governance networks. Observers have pointed to a risk of such governance arrangements being dominated by experts. This article studies the highly complex multilevel governance networks of water management in Norway, and unveils the importance of political anchorage of such governance networks at local and regional levels. The study finds evidence that political anchorage matters for further network achievements. Because the water governance networks are subordinated to the hierarchy of government, they need to 'talk to' the system of hierarchical government in order to be effective. In this regard, it seems crucial that networks are politically anchored. Furthermore, the study unveils the important role of political leadership and network managers in ensuring political anchorage.